The Association of Virulence Determinants of Uropathogenic Escherichia coli With Antibiotic Resistance - Asadi, Sara (Kowsar, 2014)
BACKGROUND: The emergence of antimicrobial resistant strains of Escherichia coli has raised considerable interest in understanding the diversity and epidemiology of E. coli infections in humans. Virulence factors of E. coli determine the specific infections caused by this microorganism. OBJECTIVES: This study aimed to determine the prevalence of eight E. coli virulence factors and their association with antimicrobial resistance in bacteria isolated from patients with urinary tract infections (UTI). PATIENTS AND METHODS: One thousand patients with UTI were enrolled in this cross-sectional study. Antimicrobial susceptibility was examined by disc diffusion method according to CLSI guidelines. After DNA extraction, the materials were probed by PCR for eight virulence factors genes, namely fimH, hly, iucC, ibeA, sfa/foc, neuC, papC, and afa genes. RESULTS: The frequency of virulence factors papC, afa, sfa/foc, fimH, hly, neuC, ibeA, and iucC were 53.3%, 51.7%, 53.3%, 56.7%, 23.3%, 31.7%, 20%, and 73.3%, respectively. In addition, there was a high degree resistance to cotrimoxazole and nalidixic acid while a high degree of susceptibility to nitrofurantoin was detected. There was a statistically significant association between fimH gene and resistance to ciprofloxacin (P = 0.006), nalidixic acid (P = 0.025), and cotrimoxazole (P = 0.02). Such associations were found between ibeA gene and amikacin (P = 0.02) and cotrimoxazole (P = 0.02) as well as between afa gene and gentamycin (P = 0.05). CONCLUSIONS: The results showed that E. coli isolated from patients with UTI had eight virulence factors with high frequencies. Moreover, these results alleged a direct connection between virulence factors and antimicrobial resistance in E. coli.